Impact of Age on tDCS Effects on Pain Threshold and Working Memory: Results of a Proof of Concept Cross-Over Randomized Controlled Study - Saldanha, Júlia Schirmer; Zortea, Maxciel; Deliberali, Cibely Bavaresco; Nitsche, Michael A.; Kuo, Min-Fang; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Aging Neuroscience, 2020)
Background: Age is an important factor that impacts the variability of tDCS effects. Objective/Hypothesis: To compare effects of anodal (a)-tDCS over the left dorsolateral prefrontal cortex (DLPFC), and primary motor cortex (M1) in adolescents, adults, and elderly on heat pain threshold (HPT) (primary outcome) and the working memory (WM) (secondary outcome). We hypothesized that the effect of tDCS on HPT and WM performance would be the largest in adolescents because their pre-frontal cortex is more prone to neuroplasticity. Methods: We included 30 healthy women within the age ranges of 15 to 16 (adolescents, n= 10), 30 to 40 (adults, n=10), and 60 to 70 (elderly, n=10) years. In this crossover single-blinded study, participants received three interventions applied over the DLPF and M1. The active stimulation intensity was two mA for 30 min. From 20 minutes of stimulation onset, the tDCS session was coupled with online n-back task. The a-tDCS and sham were applied in a random sequence, with a washout time of a minimum seven days between each trial. HPT was evaluated before and after stimulation. The WM performance with an n-back task was assessed after the tDCS session. Results: A Generalized Estimating Equation (GEE) model revealed a significant effect of the a-tDCS over the left DLPFC to reduce the HPT in adolescents compared with sham. It increased the pain perception significantly [a large effect size (ES) of 1.09)]. In the adults, a-tDCS over M1 enhanced the HPT significantly (a large ES of 1.25) compared to sham. No significant effect for HPT was found in the elderly. Response time for hits was reduced for a-tDCS over the DLPFC in adolescents, as compared to the other two age groups. Conclusions: These findings suggest that a-tDCS modulates pain perception and WM differentially according to age and target area of stimulation. In adolescents, anodal stimulation over the DLPFC increased the pain perception, while in adults, the stimulation over the M1 increased the pain threshold. Thus, they elucidate the impact of tDCS for different age groups and can help to define what is the appropriate intervention according to age in further clinical trials.